Parâmetros da marcha, pressões plantares e equilíbrio corporal de diabéticos neuropatas e vasculopatas, com o uso de palmilhas - Mantovani, Alessandra Madia [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
O Pé Diabético, resultante da neuropatia diabética periférica (NDP) associada à vasculopatia diabética periférica (VDP), é a complicação crônica mais frequente e incapacitante do Diabetes Mellitus. Dentre as medidas para prevenir ou melhorar o quadro de complicação dos pés, destaca-se o uso de calçados adequados. Diante disso os objetivos do estudo foram: a) analisar o comportamento dos parâmetros da marcha de não diabéticos e diabéticos com diferentes graus de comprometimento do pé; b) Analisar o comportamento dos parâmetros espaço-temporais e da integral pressão-tempo da marcha de diabéticos neuropatas e vasculopatas em relação ao tempo de uso de um calçado adaptado com palmilha customizada. Para tanto, no primeiro estudo participaram 68 indivíduos de 50 a 65 anos divididos em três grupos: GC - grupo controle (n=33), GN - grupo diabético neuropata (n=18) e GNV - grupo diabético neuropata e vasculopata (n=17). Inicialmente, foram realizados testes para confirmação de NDP e VDP. Em seguida, foram...

The Diabetic Foot, resulting from diabetic peripheral neuropathy (DPN) associated with diabetic peripheral vascular disease (VDP) is the most common chronic complication of Diabetes Mellitus and disabling. Among the means to prevent or improve the complications of the feet, the highlight is the use of appropriate footwear. Thus, the objectives of the study were: a) to analyze the behavior of the gait parameters of diabetic and non-diabetic patients with different degrees of commitment foot b) analyze the behavior of spatiotemporal parameters and pressure-time integral of the gait of diabetics vasculopathies and neuropathies in relation to time use a adapted shoe with custom-made insole. Therefore, the first study enrolled 68 individuals 50-65 years divided into three groups: CG - control group (n = 33), NG - diabetic neuropathy group (n = 18) and NVG - diabetic neuropathy and vasculopata group (n = 17). Initially, tests were performed to confirm the NDP and VDP. Then underwent evaluation by electronic baropodometry in the act of locomotion. The second study consisted of 50 subjects of both genders which were divided into two groups: control group (CG) (n = 33) and diabetic group (DG) (n = 17), with the latter received the footwear with... (Complete abstract click electronic access below)
Keywords: Fisioterapia; Diabetes - Prevenção; Sistema nervoso - Doenças; Vasculite; Physical therapy